Abandoning family management: Analysis of the effects on exports - Aoife Hanley; Joaquín Monreal-Pérez; Gregorio Sánchez Marín (European Journal of Family Business (EJFB), 2020)
Finding the internationalization triggers of family-managed firms is not easy because family-managed firms are regarded as being very different to begin with (e.g. Bloom et al., 2011).In investigating the role of family management, we apply a Spanish sample of 805 family-managed firms to investigate the impact of abandoning such management on export propensity. Through a Logit model, we find that such abandon is associated with a fall in export propensity, findings we relate back to managerial theories of the firm. This finding is related to specific features of family managed firms that favour export activity such as a greater flexibility and altruism. The conclusions of this work have a number of relevant implications.
Keywords: M12; M14; M16; 650; Family firm management; Management transition; Export propensity